2-Oxo-2,3-dihydro-1H-indol-3-one nicotinoylhydrazone - Basirun, Wan Jefrey; Ng, S.W.; Ali, H.M.; Halim, S.N.A. (International Union of Crystallography, 2005)
In the title structure, C14H10N4O 2, the pyridyl ring is twisted with respect to the central -C(=O)-NH-N= fragment by 17.7 (1)°, whereas the indole fused-ring system is almost coplanar with this fragment. Molecules are linked into a linear chain motif by N-H⋯O hydrogen bonds. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.